Pengembangan UMKM Ekonomi Kreatif Berbasis Food & Beverage (F&B) Pada Kelurahan Klampis Ngasem - Dinar Erika Febianti; Sumainah Fauziah (Yayasan Daarul Huda Kruengmane, 2023)
Product branding is a methodology in worldwide contests that generates plans, brand images and impressions that appeal to shoppers. The easiest thing that can be done for product branding is through a decent and attractive catalog photo. However, MSMEs that have not been able to take advantage of product branding are an obstacle for business actors in RW 09 Klampis Ngasem Village in developing their market. Most MSMEs are on average aged 40 and over which is of course very difficult to get involved in using marketing in digital business models. On this basis the community service carried out on Jl. Klampis Sacharosa, Kelurahan Klampis Ngasem by students from group 76 KKN-Thematic UPN